Assessing the Impact of Adherence on the Cost of Illness among Schizophrenia Outpatients - Suri, Nurma; Rony, Farras Qanitah (Indonesian Journal of Clinical Pharmacy, 2025)
Schizophrenia imposes a significant economic burden on both patients and their families. This study aims to evaluate the costs incurred by outpatient schizophrenia patients and examine their relationship with adherence to monthly hospital visits. An observational study was conducted at the Mental Health Hospital of Lampung Province from February to September 2023, utilizing both primary and secondary data. Primary data were collected through questionnaires assessing direct and indirect costs from the patient’s perspective, while secondary data from medical records provided information on patient demographics and hospital visit adherence. To analyse the relationship between sociodemographic variables and patient adherence, a bivariate analysis was performed using the chi square test. Meanwhile, the association between cost variables and adherence was examined using the Mann Whitney U test. The study involved 100 subjects, revealing an average total cost of illness of IDR 258,586 per patient per month or IDR 3,103,032 per year. The mean direct medical cost was IDR 123,774.26, while direct nonmedical costs and indirect costs amounted to IDR 111,277.23 and IDR 22,376.23 per patient, respectively. The analysis indicated a significant association between patient adherence and sociodemographic factors, including insurance status, the presence of a companion, and place of residence. Additionally, the patience adherence—reflected in regular hospital visits—was positively associated with both direct nonmedical costs and total illness costs. These findings suggest that reducing direct nonmedical costs, such as transportation, food, and accommodation, may help lower the overall cost of illness and ultimately improve patient adherence to regular hospital visits.